PERAN INFLUENCER DALAM PEMASARAN BANK DIGITAL DI APLIKASI TIKTOK - Eltino, Prata Besto (Universitas Sarjanawiyata Tamansiswa, 2026)
The development of digital technology has significantly transformed consumer behavior in seeking information and making purchase decisions. One notable phenomenon is the increasing influence of social media, particularly TikTok, as an effective digital marketing platform among Generation Z. This study aims to examine the effects of influencer credibility and influencer attractiveness on consumer attitudes, as well as the influence of consumer attitudes on the intention to open a SeaBank digital banking account through TikTok content. This study employs a quantitative method with a causal research design to analyze the relationships among variables. Data were collected through an online questionnaire using a Likert scale, distributed to Generation Z respondents in the Greater Jakarta area (Jabodetabek) who had viewed content from the TikTok account @doddybicarainvestasi. The data were analyzed using validity and reliability tests, followed by hypothesis testing. The results indicate that influencer credibility and influencer attractiveness have a positive and significant effect on consumer attitudes. Furthermore, consumer attitudes have a positive and significant effect on the intention to open a SeaBank digital banking account. These findings suggest that TikTok influencers play a strategic role in shaping positive consumer attitudes and increasing intentions toward digital banking services. Therefore, digital banking companies are encouraged to optimize influencer marketing strategies by strengthening credibility, transparency, and content relevance on social media platforms.